The Influence of Order Complexity and Logistics System Capability on Task-Technology Fit and Fulfillment Center Logistics System Capability: A Study on E-Commerce Fulfillment Centers - Dani Ramdani; Agus Purnomo; Erna Mulyati (Dinasti International Journal of Education Management And Social Science, 2025)
This study explores how the complexity of customer orders and the strength of logistics systems impact service quality in E-Commerce fulfillment centers, using the Task-Technology Fit (TTF) model as a framework. The research focuses on E-Commerce companies in the Jabodetabek area, gathering data from 200 employees through a quantitative method using SEM-PLS. Results show that while complex orders can improve the alignment between tasks and technology, they may reduce logistics system effectiveness. However, strong logistics capabilities enhance both TTF and service quality. The study highlights TTF as a key factor linking logistics performance to service outcomes. These findings offer both theoretical insights into the TTF model and practical guidance for E-Commerce businesses aiming to improve service efficiency by better aligning technology, logistics, and task demands.